Comparison of Common and Disease-Specific Post-translational Modifications of Pathological Tau Associated With a Wide Range of Tauopathies - Kametani, Fuyuki; Yoshida, Mari; Matsubara, Tomoyasu; Murayama, Shigeo; Saito, Yuko; Kawakami, Ito; Onaya, Mitsumoto; Tanaka, Hidetomo; Kakita, Akiyoshi; Robinson, Andrew C.; Mann, David M. A.; Hasegawa, Masato (Frontiers in Neuroscience, 2020)
Tauopathies are the most common type of neurodegenerative proteinopathy, being characterized by cytoplasmic aggregates of hyperphosphorylated tau protein. The formation and morphologies of these tau inclusions, the distribution of the lesions and related metabolic changes in cytoplasm differ among different tauopathies. The aim of this study was to examine whether there are differences in the post-translational modifications (PTMs) in the pathological tau proteins. We analyzed sarkosyl-insoluble pathological tau proteins prepared from brains of patients with Alzheimer's disease, Pick's disease, progressive supranuclear palsy, corticobasal degeneration, globular glial tauopathy or frontotemporal dementia and parkinsonisms linked to chromosome 17 with tau inclusions using liquid chromatography mass spectrometry. In pathological tau proteins associated with a wide range of tauopathies, PTMs in total were identified including new PTMs. Among them, common PTMs were localized in the N-and C-terminal flanking regions of the microtuble binding repeats and PTMs, which were considered to be disease-specific, were found in microtuble binding repeats forming filament core. These suggested that the differences in PTMs reflected the differences in tau filament core structures in each disease.